Gejala Neuropsikiatri Pasien HIV Setelah Menjalani Transisi Antiretrovirus Nevirapin ke Dolutegravir di Rumah Sakit Cipto Mangunkusumo, Jakarta - Pratama, Metra Adi; Putranto, Rudi; Herqutanto, Herqutanto; Syahrani, Aisyah; Hapsari, Aljira Fitya; Natali, Veritea; Pane, Meivina Ramadhani; Yunihastuti, Evy (Jurnal Penyakit Dalam Indonesia, 2025)
Introduction. Dolutegravir (DTG) is one of the effective antiretroviral therapies (ART) for suppressing HIV replication and has a favorable safety profile. However, reports regarding neuropsychiatric side effects, especially in patients transitioning from a nevirapine (NVP) regimen to dolutegravir, have started to emerge. This study aimed to describe the changes in neuropsychiatric symptoms before and after the transition from a NVP-based ARV regimen to DTG in HIV patients at Cipto Mangunkusumo Hospital (RSCM), Jakarta. Methods. This study employed a prospective cohort design involving 292 HIV patients at Cipto Mangunkusumo Hospital who were transitioning from NVP to DTG regimen. Participants were monitored for six months, and neuropsychiatric symptoms were assessed using a modified HIV symptom index (mHSI). Data collection was conducted at the beginning of the transition (baseline) and during follow-up through interviews regarding HIV-related symptoms and ART. Results. At the start of the study, 70.2% of participants reported at least one neuropsychiatric symptom, which increased to 80.1% after 6 months of transitioning to TLD. The most commonly reported symptoms were insomnia, headaches, and anxiety, with women reporting more symptoms than men. Statistical analysis showed a significant increase in symptoms of sadness, headaches, and irritability (p < 0.01) after the transition to dtg. Conclusions. Although DTG shows good viral suppression capabilities, significant neuropsychiatric side effects still arose, especially in patients with a history of mental disorders. Close monitoring of neuropsychiatric symptoms and adjustments to the ART regimen need to be carried out to improve the quality of life for HIV patients undergoing DTG therapy.